A Comprehensive Literature Review of Effectiveness of Supplementary Calcium in Prevention of Preeclampsia - Fajar Nurochman Sidik; Dhimas Muhammad Suharyo (The Indonesian Journal of General Medicine, 2024)
Background: The literature on the effectiveness of supplementary calcium in preventing preeclampsia indicates a consensus among researchers about its potential benefits, although the evidence is nuanced and complex. Early discussions initiated by (López-Jaramillo et al., 2001) emphasized the necessity for large, controlled trials to establish a clearer understanding of the relationship between calcium supplementation and preeclampsia prevention. The variability in methodologies across studies complicates the ability to draw definitive conclusions, as highlighted by the inconsistencies in dosage, timing, and definitions of preeclampsia (removal of unmatched citation). Literature Review: The evidence presented by (Hofmeyr et al., 2014) indicates that low-dose calcium supplementation can significantly reduce the incidence of preeclampsia, particularly in populations at risk. This is echoed in the meta-analysis by (B. Adams et al., 2021), which highlighted the essential role of calcium in regulating blood pressure, particularly among women with low dietary intake. Furthermore, the exploration of calcium's physiological mechanisms, as discussed by (Perry et al., 2022), illustrates how calcium influences vascular function and may mitigate the risk of preeclampsia through various biological pathways. The findings from (Zavala et al., 2022) also affirm the protective effect of calcium supplementation, suggesting a substantial reduction in preeclampsia risk when higher doses are administered. Conclusion: In conclusion, while there is robust evidence supporting the role of calcium supplementation in preventing preeclampsia, the complexities surrounding dietary intake, individual risk factors, and the need for tailored supplementation strategies remain significant. Future research should aim to refine these recommendations and explore the optimal conditions under which calcium supplementation can be most effective in reducing the incidence of preeclampsia.